Assessment of effective joint width for exterior eccentric reinforced concrete beam–column joints - Mahajan, Milinda Ashok; Rao, G. Appa; Sengupta, Amlan Kumar (Journal of Structural Engineering, 2025)
The response of reinforced concrete (RC) framed structures under the action of lateral loads depends on the type of joints between the framing beams and columns. The design specifications developed for concentric joints are inadequate to be used for the design of eccentric beam–column joints. This study investigated the shear deformation and strength of non-seismically detailed RC concentric and eccentric exterior joints, through experiments and nonlinear finite element analysis. From the tested specimens it was observed that in the eccentric joint, the effect of torsion increased the joint shear deformation by more than 50%, and reduced the joint shear strength by about 20%. A parametric study was carried out using the finite element analysis to model the effects of beam-to-column width ratio, joint eccentricity and joint aspect ratio on the effective width of a joint. It is found that the proposed expression of the effective width of joints predicts reasonably well, when compared with numerical and experimental values.